2019
DOI: 10.1093/jbcr/irz149
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Burn Treatment Using Tilapia Skin as a Xenograft for Superficial Partial-Thickness Wounds: A Pilot Study

Abstract: This study aims to evaluate the efficacy of Nile tilapia skin as a xenograft for the treatment of partial-thickness burn wounds in children. This is an open-label, monocentric, randomized phase II pilot study conducted in Fortaleza, Brazil. The study population consisted of 30 children between the ages of 2 and 12 years with superficial “partial-thickness” burns admitted less than 72 hours from the thermal injury. In the test group, the tilapia skin was applied. In the control group, a thin layer of silver sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 23 publications
1
43
0
3
Order By: Relevance
“…SSD [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] treatment was reported in comparison with amnion membrane (AM) [ 20 , 40 , 41 ], biosynthetic dressings (Biobrane, EzDerm, Transcyte) [ 18 , 21 , 22 , 40 , 41 , 42 , 43 , 44 ], Biobrane only [ 18 , 21 , 22 , 42 , 43 ], negative pressure wound therapy (NPWT) [ 27 , 35 , 45 ], silver foam dressings (Acticoat, Aquacel Ag, Mepilex Ag) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and Acticoat only [ 46 , 47 , 49 ], which can be seen in the following figures. The attributes of each aforementioned intervention, as well as autografts [ 41 , 52 ], Silvasorb [ 25 ], Tilapia [ 16 ], additional treatments (viz., collagenase [ 19 ], vitamin E + C + Zinc [ 53 ], wIRA [ 36 ], heparin [ 38 ], rhGM-CSF […”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SSD [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] treatment was reported in comparison with amnion membrane (AM) [ 20 , 40 , 41 ], biosynthetic dressings (Biobrane, EzDerm, Transcyte) [ 18 , 21 , 22 , 40 , 41 , 42 , 43 , 44 ], Biobrane only [ 18 , 21 , 22 , 42 , 43 ], negative pressure wound therapy (NPWT) [ 27 , 35 , 45 ], silver foam dressings (Acticoat, Aquacel Ag, Mepilex Ag) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and Acticoat only [ 46 , 47 , 49 ], which can be seen in the following figures. The attributes of each aforementioned intervention, as well as autografts [ 41 , 52 ], Silvasorb [ 25 ], Tilapia [ 16 ], additional treatments (viz., collagenase [ 19 ], vitamin E + C + Zinc [ 53 ], wIRA [ 36 ], heparin [ 38 ], rhGM-CSF […”
Section: Resultsmentioning
confidence: 99%
“…Only one multi-centre study [ 17 ] was identified. Six studies reported outcomes from II/A [ 16 , 20 , 22 , 35 , 36 , 39 ], five from II/B [ 20 , 27 , 34 , 39 , 41 ], three from II/A and MD [ 17 , 25 , 42 ] and one from MD injuries only [ 46 ], while in the remaining studies, the exact depth of the injury was not specified in children with PT burns [18,19,21,23,24,26,37.40,43–45,47,48,53]. The trial and patient characteristics of the 29 RCTs analysed in this study are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pele de tilápia-do-Nilo (Oreochromis niloticus) apresenta estrutura morfológica semelhante à pele humana, sendo a derme composta por feixes de colágeno compactados, longos e organizados do tipo I, com elevada resistência à tração (ALVES et al, 2018). Até o momento, a utilização desse biomaterial em outras áreas como cirurgia plástica, ginecologia e queimadura DIAS et al, 2019;DIAS et al, 2020;LIMA JUNIOR et al, 2020a;LIMA JUNIOR et al, 2020b;RODRIGUEZ et al, 2020) tem se mostrado eficaz, sem ocorrência de efeitos colaterais significativos.…”
Section: Introductionunclassified
“…A queda da pele de proteção era esperada em um período anterior a 7 dias, devido ao meio intra-oral ser dinâmico e úmido, sofrendo constantes traumas e interações químicas com o material. Dessa forma, o material tem uma reabsorção mais rápida do que seu uso em área externa ao meio bucal, como por exemplo, o uso da pele em queimaduras da derme, as quais devem receber a troca do material a cada 12 dias(LIMA JUNIOR et al, 2020b).As principais limitações do estudo estão na impossibilidade de cegamento do participante e do operador, já que a diferença entre os materiais é visualmente e texturalmente perceptível. Portanto, nesse estudo, apenas o examinador foi cegado.Outra dificuldade foi imposta pela decorrência da pandemia COVID-19, já que não foi possível a inclusão de maior número de participantes e grupos de estudo devido à suspensão de todas as atividades de pesquisa clínica desde março de 2020.…”
unclassified